TRADITIONAL COMMUNICATION IN BUILDING CULTURAL TOURISM: CASE STUDY OF TRADITIONAL VILLAGE IN CIBEDUG CIKOLE VILLAGE, WEST BANDUNG - Sanusi, Nunung; Susanti, Susan (TOPLAMA, 2024)
This research aims to understand the dynamics of cultural communication in Cibedug Village, Cikole, West Bandung Regency. The main focus of this research is to identify how local cultural values are maintained and influenced by communication patterns that exist within village communities.  Cibedug Village was chosen as the research location because it has unique cultural riches but continues to adapt to changing times and modernization. The research method used is a case study with a qualitative approach. Data was collected through participant observation, in-depth interviews with community leaders and local stakeholders, as well as content analysis of cultural documents and communication media used in the community. It is hoped that the results of this research will provide a deeper understanding of how communication interactions in village communities influence the maintenance and evolution of their culture. Apart from that, this research also has the potential to provide recommendations for related parties to further strengthen efforts to preserve local culture through a more effective and inclusive communication approach.